Prevalence Of Adherence To Drugs In Patients With Type 2 Diabetes In Saudi Arabia: A Systematic Review 2024 (The Review of Diabetic Studies, 2024)
Background:Diabetes Mellitus is one of the most common metabolic problems in Saudi Arabia and its chronic progressive disease is characterized by numerous health complications. Diabetes Mellitus is considered a key public health problem globally due to its incidence and prevalence and the complications therein. Globally, diabetes affects 425 million people at a prevalence of 8.8% and will rise to approximately 700 million people by the year 2040.  Diabetes often coexists with other medical conditions and is a contributing cause of death in 88% of people who have it. The primary purpose of this systematic review is to synthesize the evidence regarding risk factors associated with non-adherence to prescribed glucose-lowering agents, the impact of non-adherence on glycemic control and the economics of diabetes care, and the interventions designed to improve adherence Prevalence of adherence to drugs in patients with type 2 diabetes in Saudi Arabia . Currently, one in every 11 adults worldwide is living with the condition with 90% of these being type II diabetes patients. The past three decades have recorded a distressing rise in the cases of diabetes mellitus, resulting in quadrupling of the cases.Aim of this systematically review : To determine the prevalence of adherence to drugs in patients  in type 2diabetes patients in Saudi Arabia.Method: Online searching engines were using databases to identify relevant articles through the included electronic databases: PubMed, EMBASE, PsycINFO, and CINAHL from July 2020 to April 2024 and Saudi Digital Library (SDL), data extracted from published articles were systematically analyzed for prevalence of adherence to drugs in patients with type 2 diabetes. Results:. The usability and outcome of Prevalence of adherence to drugs in patients with type 2 diabetes in Saudi Arabia . 7 articles were selected that compliant with the theme of this present systematic review (Table 1). Among the 7 reviewed articles, articles have explained the current Prevalence of adherence to drugs in patients with type 2 diabetes in Saudi Arabia;Conclusion: The present  studies found low medication adherence by patients with T2DM regarding their prescribed diabetes medication. Low and medium adherence were significantly associated with gender, education status, and duration of diabetes. Moreover, we found that medication adherence is positively correlated with diabetes knowledge and patients’ brief perception of their diabetes status.